2017
DOI: 10.12691/jfs-5-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Texting, a Self-Assessment Technique for the Home Food Environment

Abstract: This paper explores a methodology of photo-texting to assess and improve upon the home food environment (HFE); a method which aims to engage participants with nutrition and food security among households. Various approaches to assessing and intervening within the HFE have demonstrated the efficacy of strengthening household food practices, improving food security, and dietary behaviors. However, public health practitioners face barriers in assessing the HFE. These include the intimate nature of the home settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For example, J. S. Sin Wei and Le Q. McManamey analysed the factors affecting food security of migrants on the example of Tasmania. In a study by L. Bidiger-Friedman and B. Sanchez a buying food behaviour and food insecurity of students were studied [3][4].…”
Section: Methodsmentioning
confidence: 99%
“…For example, J. S. Sin Wei and Le Q. McManamey analysed the factors affecting food security of migrants on the example of Tasmania. In a study by L. Bidiger-Friedman and B. Sanchez a buying food behaviour and food insecurity of students were studied [3][4].…”
Section: Methodsmentioning
confidence: 99%
“…L. Bidiger-Friedman and B. Sanchez studied food buying behavior and food insecurity among college students, using the example of the University of Texas at San Antonio [3]. The results showed that almost a third of the students were classified as having very low (11.6%) or low (19.4%) food security.…”
Section: Methodsmentioning
confidence: 99%